1
$\begingroup$

Solve the recurrence relation:

$u_{n+2} = 2u_{n+1}-u_n$

$u_0 = 1 $ and $u_1 = 4$

My calculations:

I have calculated that the characteristic equation is: $t^2-2t+1 = 0$ so the roots are $r_1=1$ and $r_2=1$

here is where I am stuck. The answer says that the general solution is: $u_n=(A+Bn)1^n$ But how do I know and come to that conclusion?

$\endgroup$
  • 1
    $\begingroup$ If your objective is to solve recurrence relations, that is just a fact which you should know: a second order homogeneous recurrence with equal characteristic roots $r_1=r_2=r$ has general solution $(A+Bn)r^n$. If you are looking for a proof that this is the case, please make that clear in your question. $\endgroup$ – David Mar 13 '17 at 22:55
1
$\begingroup$

$\begin{bmatrix}u_{n+2}\\u_{n+1}\end{bmatrix} = \begin{bmatrix} 2&-1\\1&0\end{bmatrix}\begin{bmatrix}u_{n+1}\\u_{n}\end{bmatrix}$

$\mathbf u_n = B^n \mathbf u_0$

Unfortunately B is not diagonalizable.

$\lambda^2 - 2\lambda + 1 = 0\\(\lambda-1)^2$

Choose $v_1$ such that $(B-\lambda I)v_1 = 0\\ v_1 = \begin{bmatrix}1\\1\end{bmatrix}$

Choose $v_2$ such that $(B-I)v_2 = v_1$

$v_2 = \begin{bmatrix}1\\0\end{bmatrix}$

$B\begin{bmatrix}1&1\\1&0\end{bmatrix} = \begin{bmatrix}1&1\\1&0\end{bmatrix}\begin{bmatrix}1&1\\0&1\end{bmatrix}\\ B = \begin{bmatrix}1&1\\1&0\end{bmatrix}\begin{bmatrix}1&1\\0&1\end{bmatrix}\begin{bmatrix}0&1\\1&-1\end{bmatrix}\\ B^n = \begin{bmatrix}1&1\\1&0\end{bmatrix}\begin{bmatrix}1&1\\0&1\end{bmatrix}^n\begin{bmatrix}0&1\\1&-1\end{bmatrix}= \begin{bmatrix}1&1\\1&0\end{bmatrix}\begin{bmatrix}1&n\\0&1\end{bmatrix}\begin{bmatrix}0&1\\1&-1\end{bmatrix}$

$\begin{bmatrix}u_{n+1}\\u_{n}\end{bmatrix} =$$ \begin{bmatrix}1&1\\1&0\end{bmatrix}\begin{bmatrix}1&n\\0&1\end{bmatrix}\begin{bmatrix}0&1\\1&-1\end{bmatrix}\begin{bmatrix}4\\1\end{bmatrix}\\ \begin{bmatrix}1&1\\1&0\end{bmatrix}\begin{bmatrix}1&n\\0&1\end{bmatrix}\begin{bmatrix}1\\3\end{bmatrix}\\ \begin{bmatrix}1&1\\1&0\end{bmatrix}\begin{bmatrix}1+3n\\3\end{bmatrix}\\ \begin{bmatrix}4+3n\\1+3n\end{bmatrix}\\$

$\endgroup$
1
$\begingroup$

$\newcommand{\bbx}[1]{\,\bbox[8px,border:1px groove navy]{\displaystyle{#1}}\,} \newcommand{\braces}[1]{\left\lbrace\,{#1}\,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\,{#1}\,\right\rbrack} \newcommand{\dd}{\mathrm{d}} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,\mathrm{e}^{#1}\,} \newcommand{\ic}{\mathrm{i}} \newcommand{\mc}[1]{\mathcal{#1}} \newcommand{\mrm}[1]{\mathrm{#1}} \newcommand{\pars}[1]{\left(\,{#1}\,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\root}[2][]{\,\sqrt[#1]{\,{#2}\,}\,} \newcommand{\totald}[3][]{\frac{\mathrm{d}^{#1} #2}{\mathrm{d} #3^{#1}}} \newcommand{\verts}[1]{\left\vert\,{#1}\,\right\vert}$

$\ds{u_{0} = 1\,,\quad u_{1} = 4}$.

\begin{align} 0 & =\sum_{n = 0}^{\infty}z^{n + 2}\pars{u_{n + 2} -2u_{n + 1} + u_{n}} = \sum_{n = 2}^{\infty}u_{n}z^{n} - 2z\sum_{n = 1}^{\infty}u_{n}z^{n} + z^{2}\sum_{n = 0}^{\infty}u_{n}z^{n} \\[5mm] = &\ \pars{-u_{0} - u_{1}z + \sum_{n = 0}^{\infty}u_{n}z^{n}} - 2z\pars{-u_{0} + \sum_{n = 0}^{\infty}u_{n}z^{n}} + z^{2}\sum_{n = 0}^{\infty}u_{n}z^{n} \\[5mm] = &\ -1 - 2z + \pars{1 - 2z + z^{2}}\sum_{n = 0}^{\infty}u_{n}z^{n} \\[5mm] \implies &\ \sum_{n = 0}^{\infty}u_{n}z^{n} = {2z + 1 \over 1 - 2z + z^{2}} = {3 - 2\pars{1 - z} \over \pars{1 - z}^{2}} = {3 \over \pars{1 - z}^{2}} - {2 \over 1 - z} \end{align}


\begin{align} u_{n} & = \bracks{z^{n}}\sum_{k = 0}^{\infty}u_{k}z^{k} = \bracks{z^{n}}\bracks{{3 \over \pars{1 - z}^{2}} - {2 \over 1 - z}} = \bracks{z^{n}}\bracks{3\sum_{k = 0}^{\infty}{-2 \choose k}\pars{-z}^{k} - 2\sum_{k = 0}^{\infty}z^{k}} \\[5mm] = &\ \bracks{z^{n}}\bracks{3\sum_{k = 0}^{\infty}{k + 1 \choose k}z^{k} - 2\sum_{k = 0}^{\infty}z^{k}} = \bracks{z^{n}}\sum_{k = 0}^{\infty}\pars{3k + 1}z^{k}\implies \bbox[15px,#ffe,border:1px dotted navy]{\ds{u_{n} = 3n + 1}} \end{align}

$\endgroup$
1
$\begingroup$

Hint: rearranging the recurrence and iterating shows an easily recognizable arithmetic progression:

$$ u_{n+2}-u_{n+1} = u_{n+1}-u_n = u_n-u_{n-1} = \cdots = u_1-u_0 = 3 $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.